Headaches in Children: A New Neurological Interpretation - Ferrante, Antonio (British Journal of Healthcare and Medical Research, 2025)
Introduction: This paper aims to shed light on an increasingly common condition, namely headaches in children. Until now, the problem has been studied to rule out the presence of underlying diseases, but without a thorough understanding of the causal mechanisms, we are groping in the dark and end up resorting to symptomatic remedies that have little to do with the phenomenon. The explanation may instead come from studying the swallowing process. Through rhythmic stimulation of the nasopalatine trigeminal receptors, this process is increasingly demonstrating its function as a regulator of the brain. Objectives: To demonstrate that headaches in children are often caused by poor swallowing function with reduced serotonin production in the brain and that re-education can solve the problem. Methods: Two groups of ten children each, all suffering from headaches for at least 10 days a month, were randomly selected. One group performed exercises to restore the ability to stimulate the palatal receptors, while the second group continued the therapies prescribed by other specialists. Results: In all participants in the working group, the headaches disappeared permanently after 45-60 days of tongue function re-education. In the control group, two people reported a reduction in the intensity of the attacks and two people reported a reduction in the number of attacks. Discussion: Myofunctional re-education proved to be a targeted therapy for headaches, as it increases the production of serotonin, which is responsible for both reducing pain perception and, to an even greater extent, reducing hypertonicity, which is the cause of tension headaches and promotes vascular headaches.